Inklusi Keuangan pada Industri Kreatif Berskala Mikro Kecil dalam Pengembangan Wilayah Masyarakat Pedesaan di Kota Binjai Provinsi Sumatera Utara - Mohammad Yusri; Abdul Rahman Cemda; Khairunnisa Rangkuti (Universitas Medan Area, 2022)
Limited access to finance is a major obstacle in the development of an area, especially rural communities. This study aims to analyze financial inclusion in the Micro Small-Scale Creative Industry towards the development of rural communities in Binjai City. This research uses a qualitative research approach with a case study method. Furthermore, a series of observations and interviews were conducted on the informants through a purposive sampling technique which was further developed through the snowball sampling technique. The results of the study inform that financial inclusion in micro-small-scale creative industries that are managed that are less educated, small-scale, have limited assets and are located in rural areas tend to have limited financing information as well as major obstacles so that the development of rural communities does not increase. The diversity of regional characteristics such as internet access and the use of financial inclusion in the creative industry, especially in obtaining banking information, alternative sources of financing that are more diverse can encourage improvements in the development of rural community areas in Binjai City. This study recommends the importance of education through training and mentoring as well as the use of the internet for Micro Small Scale Creative Industry entrepreneurs in rural Binjai City.